2015
DOI: 10.4238/2015.december.22.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolonged anesthesia with dexmedetomidine, fentanyl, or remifentanil on the self-renewal of mouse embryonic stem cells

Abstract: ABSTRACT. Previous study has indicated that exposure to anesthesia in early development leads to neuro-apoptosis and is followed by longterm cognitive dysfunction. Given that larger numbers of pregnant women currently receive anesthesia during the first trimester, we wanted to mimic this process in vitro using mouse embryonic stem cells (mESCs) and to explore how different anesthetics affect the self-renewal of mESCs. In the present study, mESCs were exposed to dexmedetomidine, fentanyl, or remifentanil at cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…35 Dex is a highly selective agonist of a-adrenergic receptors, having sedative, analgesic and anxiolytic effects at clinical doses without affecting the patient's breathing, 30 and it has been widely applied for anaesthesia in children. 7,8,36 Dex induces the activation of a2 receptors and stimulates blue-spot receptors, which can then affect the endogenous sleep pathway, mimicking the sedation that occurs in natural sleep. 37,38 Furthermore, a2 receptors in the spinal cord can also have certain analgesic effects, which will improve the recovery quality after general anaesthesia, probably by mainly reducing the occurrence of agitation during recovery.…”
Section: Discussionmentioning
confidence: 99%
“…35 Dex is a highly selective agonist of a-adrenergic receptors, having sedative, analgesic and anxiolytic effects at clinical doses without affecting the patient's breathing, 30 and it has been widely applied for anaesthesia in children. 7,8,36 Dex induces the activation of a2 receptors and stimulates blue-spot receptors, which can then affect the endogenous sleep pathway, mimicking the sedation that occurs in natural sleep. 37,38 Furthermore, a2 receptors in the spinal cord can also have certain analgesic effects, which will improve the recovery quality after general anaesthesia, probably by mainly reducing the occurrence of agitation during recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al observe that fentanyl wasn’t significantly effective in a decrease of the expression of OCT4 and SOX2 , though there was an occasional decrease. In comparison, the expression of OCT4 and SOX2 remained unchanged in the remifentanil treatment groups [ 56 ]. Furthermore, Kocak and colleagues agree with the results, and also showed that the expression of BAX , BCl2 , OCT4 , SOX2 , and Nanog genes in MCF7 cancer stem cells can be decreased with fentanyl treatment.…”
Section: Discussionmentioning
confidence: 99%
“…So, the observations support the idea that regulation of the cell cycle and maintenance of mESCs can be performed by fentanyl, which leads to its contribution to proliferation and differentiation. Clues extracted from this evidence are useful in rationalizing the mechanisms that explain the effects of fentanyl on mESCs [ 56 ].…”
Section: Discussionmentioning
confidence: 99%